AB1482-PARE Participation in clinical trials has a positive impact on the psychological and employment well-being of patients with inflammatory arthritis. (12th June 2018) - Alkoky, H; Tierney, C.; Ramasamy, V.; Knight, P.; Ingram, E.; Aconstaninesei, S.-E.; Pakozdi, A.; Abbye-Nayake, Y.; Tahir, H.
Abstract : Background: Biologic therapies have improved the physical well-being of patients with Inflammatory arthritis. However, there remains a lack of emphasis on addressing patients' psycho-social needs in routine rheumatology practice. Objectives: The aim of this study was to explore the unmet psychological, emotional and social needs of inflammatory arthritis patients (Rheumatoid Arthrirtis (RA), Psoriatic Arthritis (PsA), Axial Spondyloarthritis(AS)) entering clinical trials, and to evaluate the factors leading to improvement in physical and psychological wellbeing during the clinical trial. Methods: A cross sectional survey was distributed to all inflammatory arthritis patients having completed a minimum of 12 weeks of treatment within phase II and III clinical trials, in Whipps Cross University Hospital, between Nov 2017 and . Jan 2018 The anonymous survey included satisfaction scales with scores ranging from 0 to 10 (0=extremely dissatisfied and 10=extremely satisfied) to rate physical (ie: improvement in joints pain and swelling) and psychological satisfaction during the clinical trial. Factors contributing to patients' physical and psychological improvement were also explored. Employment status and changes were also explored. Results: A total of 46 questionnaires were completed with 5 excluded from analysis due to missing data. Of the 41 patients, 26 (63%) had PsA, 3 (7%) AS, and 12 (29%) RA. 22 (54%) patients were male. 26 (63%) patients were white caucasian, 9 (21%) were Asian and 6 (15%) were from other ethnic backgrounds. 71% of the patients were aged between 36–60. 37 (90%) of patients were satisfied with their physical improvement (joint pain and swelling) during the clinical trial. 34 (83%) said their inflammatory arthritis had a negative impact on their psychological well-being, however 39 (96%) were satisfied with the emotional support received from the clinical research staff. The most frequently reported factors contributing to their psychological improvement included, in all patients (41, 100%), the involvement of the clinical research staff and the frequency of regular follow ups. In 40 (98%) patients, the clinical research doctor and the clinical research environment and in 36 (88%) patients the study drug itself. Regarding employment status, 29 (71%) were employed prior to participating in the clinical trial, and 18 (44%) reported improvement in their employment situation after entering the clinical trial. These included new job positions, 5 reduction in sick leave days, 5 and the capability of working more hours. 1 Conclusions: Inflammatory arthritis is associated with a high prevalence of psychological burden. Addressing the physical needs solely and ignoring the psychological wellbeing of patients can adversely affect their quality of life. The current survey highlighted that by participating in clinical trials, the majority of inflammatory arthritis patients, gained additional satisfaction with regards to their psychological and emotional needs and received invaluable support within the trial setting. This led to improved well-being and employment satisfaction. We would therefore, encourage health care professionals to invest in the psychological and emotional wellbeing of patients in routine clinical practice. Disclosure of Interest: None declared